Spontaneous coronary artery dissection: a rare cause of acute coronary syndrome - Junpaparp, Parichart (BMJ Publishing Group, 2014)
Spontaneous coronary artery dissection (SCAD) is a rare cause of acute myocardial infarction, which should always be included in differential diagnoses of acute coronary syndrome among young patients without known atherosclerotic risk. Although, it is commonly observed in young women during postpartum period, there were cases reported in connective tissue disorders, eosinophilic arteritis, contraception use, cocaine abuse and repetitive chest trauma. We report a case of SCAD, presenting with acute ST-elevation myocardial infarction, which was successfully treated conservatively.